2022
DOI: 10.1177/14613484221086373
|View full text |Cite
|
Sign up to set email alerts
|

Vibration characteristics of channel steel-concrete composite girders: An experimental and numerical analysis

Abstract: The broad application of steel and steel-concrete bridges has caused significant vibration and noise problems. Although the channel steel-concrete composite girder is a commonly used bridge type, the vibration transmission performance and structural optimization design (concrete deck, stiffeners, transverse connection components, etc.) from the perspective of vibration control have not been well studied. In this paper, experimental and numerical approaches are combined to investigate the dynamic properties of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…They found that the noise generated by the steel girders was dominant in the high-frequency range above 315 Hz, whereas the noise generated by the concrete deck was dominant in the low-frequency range of 80–160 Hz. Zhang et al 5 used FEM to examine the vibration spectra of a steel–concrete composite girder structure and, via a comparison with the experimental results, showed that adding a concrete deck to the steel girders could effectively reduce the deck vibration. The aforementioned studies predicted SBN via the combined advantages of FE and BEM/SEA modeling to deal with near-field structure vibration and far-field noise propagation, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the noise generated by the steel girders was dominant in the high-frequency range above 315 Hz, whereas the noise generated by the concrete deck was dominant in the low-frequency range of 80–160 Hz. Zhang et al 5 used FEM to examine the vibration spectra of a steel–concrete composite girder structure and, via a comparison with the experimental results, showed that adding a concrete deck to the steel girders could effectively reduce the deck vibration. The aforementioned studies predicted SBN via the combined advantages of FE and BEM/SEA modeling to deal with near-field structure vibration and far-field noise propagation, respectively.…”
Section: Introductionmentioning
confidence: 99%